The Effect of Instructional Methods and Cognitive Styles toward Speaking Skill - Nita Kaniadewi (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2017)
This study investigated the effect of instructional methods and students’ cognitive styles toward speaking skill. It was an experimental research using a two-factor ANOVA at 0.05 and 0.01 significance level. Because an interaction between the variables involved was found, the analysis was then continued by Tuckey Test. The data was collected using oral test rating scale and a cognitive style questionnaire. The findings showed the following points: (1) the speaking skill of the students taught by CLL (Cooperative Language Learning) was higher than the students taught by TBL (Task-Based Language Learning); (2) the speaking skill of FD (Field Dependent) students was higher than FI (Field Independent) students; (3) there was an interaction between instructional methods and cognitive style to speaking skill; (4) the speaking skill of the students taught by CLL was higher than the students taught by TBL in the group of FD students; (5) there was no significant difference of the speaking skill of the students taught by CLL and the students taught by TBL in the group of FI students. The findings above led to a conclusion that generally CLL was more effective than TBL in teaching speaking skill. Moreover, besides instructional methods, cognitive style also gives a significant effect to students’ speaking skill.